Long-Term Forecasting of the Spa And Wellness Subsector of the Bulgarian Tourism Industry - Dimitrov,Preslav (2011)
In the past twelve years Bulgaria has managed to capitalize on the good results achieved in certain subsectors of its tourism industry, such as the spa and wellness industry. The fluctuations in the international tourism markets due to the world economic crisis, however, still provoke hesitations for the investors in the Bulgarian tourism industry. This uncertainty and the fear of possible negative outcomes in Bulgarias spa and wellness tourism could be diminished if there are comparatively true long-term forecasts for what is to happen in the coming 10 or 12 years. The present paper regards the application of some forecasting methods in the spa and wellness sub-sector of the Bulgarian tourism industry such as linear trend forecasting and double exponential forecasting (Holts method). A specially designed model for estimation of the weight coefficient needed for determining the size of the sector of the spa and wellness tourism in the time series of the available data and in the forecast values is presented. A time series and past period predictions have been constructed based on statistical records since 1964 in order to test the forecasting methods presented in the paper and to produce forecasts up to the year 2022.